Performance analysis of AO‐OFDM‐CDMA with advanced 2D‐hybrid coding for amplifier‐free LR‐PONs. Issue 6 (1st December 2018) - Mrabet, Hichem; Mhatli, Sofien; Dayoub, Iyad; Giacoumidis, Elias
Abstract : All‐optical orthogonal frequency division multiplexing (AO‐OFDM) and optical code‐division multiple‐access system (OCDMA) are combined in the first analytical model, which considers subcarrier hopping by means of advanced two‐dimensional (2D) hybrid‐coded (2D‐HC) signature. The model incorporates probabilistic subcarrier overlapping, multiple‐access interferences and is tested, for the first time, over amplifier‐free long‐reach passive optical networks (LR‐PONs) using cost‐effective intensity modulations and direct detection. For the upstream direction at 40 Gb/s, AO‐OFDM‐OCDMA outperforms a 'classical' multi‐channel OCDMA system for low received powers and any number of simultaneous users. In comparison to conventional 1D Walsh–Hadamard, 1D prime code and 2D prime hop system, coding with 2D‐HC can improve the performance of AO‐OFDM‐CDMA, thus allowing a higher number of simultaneous users in LR‐PON without optical amplification. From numerical simulations, the authors show that 16‐quadrature amplitude modulation (16‐QAM) AO‐OFDM‐CDMA with 45 users has comparable performance to conventional multi‐channel 16‐QAM coherent optical OFDM in the downstream direction and up to 58 km with 1:45 split ratio, without employing complex coherent technology. Similarly, based on the feasibility of physical implementation configuration, a budget power calculation is performed showing 108 km as maximum reachability distance for 40 Gb/s QAM signal, 1:64 split ratio when considering standard forward‐error‐correction.